Effect of Drug Loading and Plasticizer on Drug Release from Polylactic Acid Film (مجلة البحوث الأكاديمية, 2019)
The objective of this study was to evaluate the effect of drug loading and plasticizer level on the release kinetic from films composed of polylactic acid (PLA). First, the polymeric film of polylactic acid of 50 % low and 50% high molecular weights with different drug loadings (20, 25 and 30%) was prepared without the plasticizer Dibutyl sebacate (DBS) to evaluate the drug (pentoxifylline) release from the polymeric matrix. Secondly, the plasticizer (DBS) with different levels (10, 20 and 30 %) was added to the formulation and the drug release from the polymeric film was evaluated. Differential Scanning Calorimetry was used to characterize and study thermal behavior of the film and the drug. Gel Permeation Chromatography GPC was used to characterize the molecular weight of the polylactic acid. Scanning Electron Microscopy was used to characterize the film surface at different drug loadings. X-ray powder diffraction was used to measure crystals peaks of the drug and the polylactic acid. The effect of plasticizer on the drug release rate has a different effect based on the drug loading levels, at low drug loading level (10 and 20%), as plasticizer level increases the drug release rate , while at high drug loading (60% ) the drug release rate decreases as the plasticizer level increases.